Implementation of Transparency Principles in Handling Public Complaints at the Enrekang Police Headquarters - Intan, Nur; Hanafi, Nurharsyah Khaer; Herman, Herman; Najamuddin, Najamuddin (Universitas of Muhammadiyah Makassar, 2025)
This study examines the growing public demand for transparency in public complaint services at the Enrekang Police Department, where challenges such as discriminatory practices and inadequate technological infrastructure persist. The research aims to evaluate the implementation of transparency principles in complaint handling services and to identify the internal and external factors influencing these processes. A qualitative research method employing a case study approach was utilized, incorporating in-depth interviews, participatory observations, and document analysis to ensure data triangulation, with thematic analysis applied for data interpretation. The findings reveal that although the Enrekang Police have made notable improvements in responsiveness, speed, and accuracy demonstrated through courteous interactions and diligent case handling significant shortcomings in timeliness remain. These delays are primarily attributed to discriminatory practices and technological constraints. The study concludes that achieving transparency in public services necessitates not only procedural and technical advancements but also a cultural transformation within the institution. It further suggests that continuous human resource development, digital innovations such as mobile case-tracking systems, and participatory public education are critical to bridging the gap between transparency ideals and practical implementation. These strategies offer a pathway toward enhancing public trust and strengthening institutional accountability.